Analisis Malware pada Perangkat Android Menggunakan Tools Mobsf (Mobile Security Framework) - Abdul Sakti; Dafrid Cahyadi Arifin (Jurnal Teknik Informatika dan Teknologi Informasi, 2025)
The rapid development of mobile technology has significantly increased the global use of Android devices. However, the open-source nature of the Android operating system makes it vulnerable to malware attacks, especially from applications downloaded through unofficial sources. This study aims to analyze potential malware threats in Android applications using the Mobile Security Framework (MobSF) tool through static and dynamic analysis approaches. Five Android application samples (APK) were analyzed, consisting of apps obtained from both the Google Play Store and third-party websites. The results indicate that applications from unofficial sources carry higher security risks, as evidenced by excessive permissions, modified file structures, and communication with suspicious servers. In contrast, applications from official sources generally showed safer results, although minor vulnerabilities were still identified. MobSF proved to be effective in detecting suspicious behavior and provided security scores that can serve as references in application evaluations. This study emphasizes the importance of conducting security audits on mobile applications prior to widespread use and encourages the utilization of MobSF as a reliable tool for security analysis in Android application development and distribution.